A bibliometric analysis on yields, zakat payment, and weighted average cost of capital for sukuk investment. - Yusri, Dila Sharina; Mohd Saad, Noriza; Mohamed, Zulkifli (Journal of Islamic, Social, Economics and Development, 2025)
This paper presents a condensed bibliometric analysis of Zakat in Sukuk investments and the Weighted Average Cost of Capital (WACC) within Islamic finance, aiming to highlight influential works, authors, institutions, and emerging trends. Using data from the Scopus database (2012-2023) and tools like VOSviewer and Harzing Publish or Perish, the study applies network visualization, bibliographic coupling, co-citation analysis, and citation metrics to uncover key patterns and trends in the literature. Findings indicate that Zakat in Sukuk investments and WACC are growing areas of interest, reflecting their significance in promoting social justice, sustainable development, and risk management in Islamic finance. The study reveals prominent contributors, collaboration networks, and dominant themes, notably the integration of Zakat in ethical investing and WACC’s role in evaluating investment feasibility and managing financial risk. To ensure methodological rigor, the PRISMA guideline was followed, detailing criteria for record inclusion and exclusion, and reasons for the removal of non-relevant records are provided. Key themes were generated through a systematic thematic analysis, emphasizing the alignment of financial practices with Islamic ethical principles. The paper concludes with implications for future research, policy recommendations, and practical applications, advocating for further exploration of these topics to enhance investment frameworks and promote socially responsible finance within the field of Islamic finance.